Rare Tauopathies - Ali, Farwa; Josephs, Keith (Seminars in Neurology, 2019)
Tauopathies are rare neurodegenerative disorders related to microtubule-associated protein tau, which functions to stabilize microtubules. Pathological changes caused by overexpression or hyperphosphorylation of tau lead to the disengagement of tau from microtubules and accumulation of toxic intracellular inclusions. Tau pathology is the underlying mechanism for several sporadic and genetic disorders. These are collectively known as tauopathies. Each tauopathy is differentiated from others by its neuropathological features such as the presence of specific isoforms of tau, type of cellular inclusions, and the regions of the brain affected. Neuropathological features, with a few exceptions however, do not correspond to distinct clinical phenotypes. There is considerable phenotypic overlap between the different tauopathies. Interaction between tau and other protein inclusions further alters the clinical phenotype.Recent advances in the development of tau biomarkers, especially the development of tau radioligands used in positron emission tomography neuroimaging, and a better understanding of biology and pathology of tau are important first steps toward the ultimate goal of accurate diagnosis and disease modification in tauopathies.
Keywords: tau; tau-PET; MAPT; FTLD-tau